2004
DOI: 10.1079/bjn20041247
|View full text |Cite
|
Sign up to set email alerts
|

Trends in energy and macronutrient intakes, body weight and physical activity in female university students (1988–2003), and effects of excluding under-reporters

Abstract: The present study investigated trends in reported energy intake, macronutrient intake, physical activity level (PAL) and body weight and effects of excluding under-reporters (UR). Dietary intake and time spent in sixteen activity categories were recorded by 887 female university students (median age 29 years) from 1988 to 2003. Energy expenditure (EE) and PAL were measured using a factorial method. All data collected were self-reported. Individuals with reported EI:EE , 0·76 were classified as UR. The remainde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
2
17
1
Order By: Relevance
“…With the exception of a decrease in total energy intake and an increase in fish consumption in men, controlling for energy underreporting did not substantially affect secular trends, neither in food consumption nor in the proportion of men and women meeting recommended national nutrient and food intakes. Our findings are in line with previously reported data showing that some, but not all, dietary trends are affected by the exclusion of energy underreporters [6,26] . However, study findings on energy underreporting vary widely, depending on the characteristics of the population studied and the method used to identify energy underreporters [27] .…”
Section: Secular Trends In Food Intakesupporting
confidence: 83%
See 1 more Smart Citation
“…With the exception of a decrease in total energy intake and an increase in fish consumption in men, controlling for energy underreporting did not substantially affect secular trends, neither in food consumption nor in the proportion of men and women meeting recommended national nutrient and food intakes. Our findings are in line with previously reported data showing that some, but not all, dietary trends are affected by the exclusion of energy underreporters [6,26] . However, study findings on energy underreporting vary widely, depending on the characteristics of the population studied and the method used to identify energy underreporters [27] .…”
Section: Secular Trends In Food Intakesupporting
confidence: 83%
“…However, study findings on energy underreporting vary widely, depending on the characteristics of the population studied and the method used to identify energy underreporters [27] . In contrast to other studies [26,28] , we found a significant decrease in the prevalence of energy underreporting (from 28.8% in 2000 to 26.6% in 2005). It is interesting to note that participants identified as energy underreporters were older, with higher BMI and lower levels of physical activity than plausible reporters.…”
Section: Secular Trends In Food Intakecontrasting
confidence: 56%
“…Using such a method has limitations because it does not empirically measure children's energy expenditures, it does not consider the amount of time being physically active, and does not measure the type of physical activity (69,70) . A number of studies have also shown that overweight or obese individuals tend to under-report their dietary intake to a greater extent than lean individuals (71)(72)(73) . Likewise, parents may be under-reporting their children's intake, particularly for snacks rather than meals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 24-h dietary recall is often recognized as the best method to estimate dietary intake, some limitations include the reliance on participants' memory, how well selected days represent usual intakes, and the possibility of under-reporting of food intakes (45). A number of studies have shown that overweight or obese individuals tend to under-report to a greater extent than lean individuals (46)(47)(48). Likewise, parents may be under-reporting their children's intake, particularly for snacks rather than meals (49,50).…”
Section: Discussionmentioning
confidence: 98%